Governing the new NHS : issues and tensions in health service policy, governance, and management - Storey, John , 1947-; Bullivant, John; Corbett-Nolan, Andrew (Routledge, 2011)
Sweeping changes have made NHS governance a crucial and contested issue. This text describes and assesses the NHS governance arrangements and accountabilities. It examines how they are working in practice, reporting on how practitioners are responding to the difficulties and paradoxes that arise